Influence Of Education Costs, Educators, Service Quality And Facilities Guardian Satisfaction At The Yayasan Tasik (Taman Anak Sholeh Ibnu Katsir) Batam - Putri Indah Safina; Septa Diana Nabella; Muhammad Rahmat; Sabri Sabri; Andi Amang (International Journal of Economics, Business and Innovation Research, 2024)
The Studies were carried done to determine how much impact educational costs, teaching staff, amenities and excellent service have on the contentment of parents in the Yayasan Tasik (Taman Anak Sholeh Ibnu Katsir) Batam. This research was carried out using a survey method with a Google Form questionnaire to the parents of the Batam Sholeh Ibnu Katsir Children's Foundation (TASIK) Foundation (TASIK) with a sample size of 40 parents. The technique for sampling uses a method of sampling (Census / Saturated), namely sample selection method If every person in the population is sampled. Hypothesis methods are analyzed using statistical techniques, namely validation tests, reliability tests, determination tests, simple regression tests, multiple regression analysis tests, T statistical tests, and F statistical tests, using the SPSS For Windows Version 25 application. The research results show that tuition fees have a negative and insignificant effect on parent satisfaction. Educators have a noteworthy and favorable influence on the contentment with student parentsThe service excellence has a substantial and favorable impact on parent contentment. Facilities have a positive and significant effect on parent contentment.